Reconciling Traditions: The Role of Local Wisdom in Mediating Divorce in Indonesia's Religious Courts - Rosdalina Bukido; Sjamsuddin A. K. Antuli; Nurlaila Harun; Nurlaila Isima; Ulin Na'mah (Khazanah Sosial, 2024)
In response to escalating divorce rates in Indonesia, particularly within its Religious Courts, this study explores the limitations of current mediation practices. It proposes local wisdom-based mediation as an alternative approach. Traditional mediation within these courts often fails to prevent divorces effectively, prompting the need for innovative solutions that integrate cultural insights. This research aims to assess the effectiveness of mediation processes within Indonesia's Religious Courts and investigate the potential role of religious leaders in improving mediation outcomes. Specifically, it highlights how local wisdom can be leveraged to mitigate divorce rates by fostering reconciliation and resolving disputes outside formal legal procedures. Using an empirical approach, researchers collected data by interviewing 50 informants, namely judges, religious leaders, and the government, related to the increasing divorce rate. The findings that can be presented are that religious figures, as locals, can reconcile divorced parties without the need to go to religious courts. The Religious Court is seen as a formal facility to certify the divorce of both parties, but has yet to be able to prevent divorce optimally. That is, the high divorce rate in religious courts requires the involvement of religious leaders in reconciling parties who want to divorce. This study accepts the potential for integrating local wisdom in mediating to reduce divorce rates. With an emphasis on cultural sensitivity and community involvement, this approach aims to go beyond the limitations of conventional legal frameworks and promote more meaningful outcomes in resolving marital conflict.